HUBUNGAN USIA DENTAL DENGAN PUNCAK PERTUMBUHAN PADA PASIEN USIA 10-14 TAHUN DI RSGM UNSYIAH - Rafinus Arifin; Putri Rahmi Noviyandri; Fara Mufti Lusmana (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractIn orthodontic treatment knowing pubertal growth spurt is very important, because in this period malocclusion will be easier to correct and the results will be better. Dental age is one of many indicator to estimate human pubertal growth spurt which can be assessed by the stages of dental emergence and calcification. The purpose of this study was to determine the relationship of dental age with pubertal growth spurt in patients of RSGM Unsyiah. This study used cross-sectionals method involving 94 girls patients aged 10-12 years and 43 boys patients aged 12-14 years in RSGM Unsyiah period June 2012-June 2014. Data collected in secondary data, they are panoramic photo and patient dental record. Evaluation of dental age was based methods of Lorenzo (2008) by eruption of canines, premolars, and second molar permanent teeth, then grouped into late mixed dentition (eruption of the canines and premolars) or early permanent dentition (eruption of second molars pemanent). Chi-Square tests were used to determine the relationship between dental age and pubertal growth spurt. Results of Chi-square test indicates a significant relationship between dental age and pubertal growth spurt p= 0.008 (p0.05). Conclusion is there is a significant relationship between dental age and pubertal growth spurt.Keyword: Pubertal growth spurt, dental age, dental emergence, dental calcification.